Genetic variability, character association and path analysis for yield components in ginger (Zingiber officinale Rosc.) - DOBHAL, G PANDEY, V K (Journal of Spices and Aromatic Crops, 1993)
Twentynine collections of ginger (Zingiber officinale) were studied for variability, character association and path analysis for yield and its 10 component characters. Wide range of variability was observed for most of the characters studied. Rhizome yield per plant was positively associated with plant height, number of fingers per plant ,weight of fingers and weight of primary rhizome. Plant analysis revealed that weight of fingers, width of fingers and leaf width were the strongest forces influencing yield.